Selective Anterior Fusion Surgery Does Not Influence Global Spinal Sagittal Alignment in Lenke Type 5 Adolescent Idiopathic Scoliosis Patients. Issue 3 (11th May 2021) - Okubo, Toshiki; Konomi, Tsunehiko; Yanai, Yoshihide; Furukawa, Mitsuru; Fujiyoshi, Kanehiro; Yamane, Junichi; Asazuma, Takashi; Yato, Yoshiyuki
Abstract : In Lenke type 5 adolescent idiopathic scoliosis patients, various global spinal sagittal alignment did not significantly change after selective anterior spinal fusion, which could maintain excellent correction for coronal deformity with satisfactory final functional and clinical outcomes for long-term follow-up. Abstract : Study Design: Retrospective comparative study. Objective: The aim of this study was to evaluate the changes in global spinal sagittal alignment (GSSA) following selective anterior spinal fusion (ASF) in patients with Lenke type 5 adolescent idiopathic scoliosis (AIS). Summary of Background Data: Few studies have assessed the changes in postoperative GSSA, including cervical, thoracic, and lumbosacral sagittal alignment in AIS patients with major thoracolumbar/lumbar (TL/L) curve who underwent selective ASF. Methods: Fifty-two patients with Lenke type 5 AIS (two males and 50 females, mean age at surgery of 16.4 ± 3.1 years) were included in this study. The average final follow-up was 8.3 ± 3.1 years after surgery. The variations of outcome variables were analyzed in various spinal sagittal profiles using radiographic outcomes (pre-operation, immediate post-operation, and final follow-up). The clinical outcomes at the final follow-up were assessed using Scoliosis Research Society (SRS)-22 and Oswestry Disability Index (ODI) questionnaires. Results: The mean Cobb angle of the main TL/L and minor thoracic curve was significantly improved after selective ASF, which was maintained up to the final follow-up. However, in all cases, the various sagittal parameters examined (sagittal vertical axis [SVA], C2–7 SVA, C2–7 lordosis, T1 slope, thoracic kyphosis, T10-L2 kyphosis, lumbar lordosis, pelvic incidence, pelvic tilt, and sacral slope), did not significantly change in the immediate postoperative period, and all GSSA parameters were maintained up to the final follow-up. Furthermore, the magnitude of coronal curve correction and fused levels did not affect each GSSA parameter postoperatively. During the period up to the final follow-up, no significant clinical symptoms were observed. The final SRS-22 global score was 4.5 ± 0.3, and ODI scored 0.8 ± 2.4. Conclusion: Selective ASF did not influence various GSSA parameters postoperatively and could maintain excellent correction for coronal deformity with satisfactory final functional and clinical outcomes confirmed by long-term follow-up. Level of Evidence: 4